Oral healthcare issues in rural residential aged care services in Victoria, Australia. (4th April 2012) - Tham, Rachel; Hardy, Susan
<x xml:space="preserve">Abstract</x> doi: 10.1111/j.1741‐2358.2012.00652.x Oral healthcare issues in rural residential aged care services in Victoria, Australia Objectives: To identify major issues in providing and accessing oral health care in Victorian rural residential aged care services from the perspectives of dentists, aged care staff and residents. Methods: Structured interviews were conducted with five dentists, nine aged care staff and six residents. Three focus groups were conducted with aged care staff. These data were thematically analysed independently by two researchers. Results: The challenges reported by dentists included complexity of care, infrastructure needs and need for skill development. Aged care staff reported lack of skills and confidence in providing oral hygiene care, especially in residents with natural teeth, and an increasing burden on their daily workload. Residents reported concern and shame regarding their declining oral health status and increased challenges accessing appropriate oral health care. Conclusion: These findings indicate the need to build and sustain aged care 'oral health teams' who are able to provide daily oral hygiene care for residents and mentor other staff. Rural dentists need access to gerodontic training, portable equipment and appropriate workspaces in aged care services. Aged care and oral health services need to establish clear referral and communication pathways.